synchronization mechanism for multi- core processors - P.R, Poornima; Devi Ge, Padmaja; Kubde, Rohan (International Journal of Engineering and Technology, 2018)
The latest trend in processor design development to get the higher performance is to integrate multiple cores into a single IC or onto multiple dies but in a single chip package. The architectures of the microcontrollers need to look the strict demand within the embedded word. For essential writing, the concurrent programs the heart of multi-core revolution is shared data synchronization. Ideally, synchronization ought to be able to exploit accessible cores for its excellent performance. In this project, tend to present a design for hardware supported synchronization unit that would be enforced on chip and that should be directly accessible by all the various multiple cores. A hardware module memory access controller is used here. It has additionally seen that dual-ported memory will provide the better performance if the multiple cores use inherent parallelism by locking the shared memory by using the tactic called address sensitive method.Â
Keywords: Multi-Core Processor; Synchronization; Dual-Ported Memory.